Development of an education simulator for particle swarm optimization in solving economic dispatch problems / Mohd Hafiz Mat Hussain - Mat Hussain, Mohd Hafiz (2009)
Development of an Educational Simulator presents a windows-based educational simulator using graphical user interface (GUI) for solving Economic Dispatch (ED) problems. The developed simulator incorporated particle swarm optimizations (PSO) to solve the ED problems. The objective of ED is to obtain the minimum generation cost with optimal power generator output while satisfying several constraints. In the developed simulator, users are able to set the parameters that have influences on particle swarm optimization performance. The Graphical User Interface (GUI) program design and PSO algorithm used in this study was implemented by using MATLAB 7.6.0 (R2008a).